1999
DOI: 10.1055/s-0037-1614532
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Components of the Fibrinolytic System in the Formation and Removal of Thrombus Induced by Endothelial Injury

Abstract: SummaryThe role of fibrinolytic system components in thrombus formation and removal in vivo was investigated in groups of six mice deficient in urokinase-type plasminogen activator (u-PA), tissue-type plasminogen activator (t-PA), or plasminogen activator inhibitor-1 (PAI-1) (u-PA-/-, t-PA-/- or PAI-1-/-, respectively) or of their wild type controls (u-PA+/+, t-PA+/+ or PAI-1+/+). Thrombus was induced in the murine carotid artery by endothelial injury using the photochemical reaction between rose bengal and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 32 publications
(33 reference statements)
2
34
0
Order By: Relevance
“…It shifts the balance between thrombosis and fibrinolysis, favoring thrombosis. 12,13 It portends an increased risk of MI. 14 Insulin increases synthesis and concentrations of PAI-1 in blood, 1520 as do mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It shifts the balance between thrombosis and fibrinolysis, favoring thrombosis. 12,13 It portends an increased risk of MI. 14 Insulin increases synthesis and concentrations of PAI-1 in blood, 1520 as do mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Clot lysis experiments confirmed that the endogenous thrombolysis potential is significantly enhanced in α2-AP -/-mice, indicating a physiological role of α2-AP in fibrin surveillance [38]. We have previously reported that tPA increases the rate of clot lysis after endothelial injury [34] and other study showed the functional significance of α2-AP as a direct inhibitor of tPA, which explains the basis of the accepted role of α2-AP as a regulator of fibrin persistence and thrombus resistance to lysis [39].…”
Section: Pulmonary Embolismmentioning
confidence: 55%
“…We found that deficiency in α2-AP led to different result in formation and removal of arterial and venous thrombus in mice [30,31]. Indeed, we applied an experimental procedure to induce endothelial injury both in the murine carotid artery and jugular vein [32][33][34]. The time to occlusion by the development of thrombus in the carotid artery was slightly prolonged in α2-AP -/-mice, whereas it was markedly prolonged in jugular vein, compared with wild type mice [30].…”
Section: Arterial and Venous Thrombusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have alluded to this possibility. Matsuno et al39 found that Plg-deficient mice had shorter arterial occlusion times after photochemical carotid injury (Table 1) whereas a deficiency of α 2 -AP, PAI-1, or vitronectin deficiency resulted in delayed occlusion times 39–42. Patency of the injured carotids was more rapid in the PAI-1 and AP-deficient mice than wild-type (WT) mice (Table 1).…”
Section: In Vivo Evidencementioning
confidence: 99%